The Beneficial of Green Beans Extract on Production of Postpartum Breast Milk in East Langsa Public Health Center 2019 - Idwar,; Magfirah,; Nasution, Irma Yuliana (International Journal of Psychosocial Rehabilitation, 2020)
Green bean extract is believed to have a beneficial on the health and production of post-partum maternal milk. To prove this advantage, a series of experimental studies have been carried out with the aim of analyzing the effect of giving green bean extract on mother's milk production. This study used a quasi-experimental approach involving the second day, postpartum mothers, with inclusion and exclusion criteria. Sampling was done by purposive sampling totaling 32 people divided into control and intervention or experimental groups. The results showed there were differences in the average value of breast milk production in the intervention and control groups with a p-value of 0.012. The provision of green bean juice affects the production of maternal milk for postpartum mothers in the work area of the Eastern Langsa Public Health Center. While the maternal age factor and the frequency of breastfeeding infants proved to be no difference in the average difference in maternal milk production in the intervention and control groups with a p-value of 0.154 and a p-value of 0.381.